Can Peptides and Gut Microbiota Be Involved in the Etiopathology of Obesity? - Aydin, Suleyman (Springer, 2017)
[Abstract Not Available]
Keywords: Intestinal Microbiota; Bariatric Surgery; Classification; Cellulase; Criteria; Hormones; Ghrelin; Release